Effectiveness of Positive Reinforcement Techniques For Increasing Concentration in Communication When Interacting with ADHD Children in SLB X Bontang City - Suprianto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This reserach is motivated by observing a child with ADHD who experiences difficulties with concentration during communication when interacting. The aim of this research is to improve concentration in communication during seated interactions for children with ADHD at SLB X in Bontang City. This research employs an experimental design in the form of single-subject research with an A-B-A design. The research subject is a child with ADHD who exhibits hyperactive symptoms and is unable to concentrate during communication. The data collection technique used in this study involves measuring the duration to assess how long the child can maintain concentration in two-way communication over a 30-minute learning or interaction period. Data analysis employs visual graph techniques. The results indicate that positive reinforcement techniques can enhance concentration during communication for children with ADHD at SLB X in Bontang City, as evidenced by the data analysis results in both the condition and between conditions."